FENOMENA BRAIN ROT DALAM PERSPEKTIF AL-QUR’AN: STUDI QUR’AN TEMATIK TERHADAP DEGRADASI KOGNITIF DI ERA DIGITAL - Adam Mustaqim Jiddan; Muhammad Alif (Adisam Publisher, 2026)
Advances in digital technology and social media have significantly changed the way people consume information. The ease of access to various types of digital content contributes to a phenomenon known as